Does free cash flow moderate the effect of profitability and capital structure on company value? - Mangku, I Ketut; Patonangan, Markliv; Najmudin, Najmudin; Susanti, Fatonah Eka (International Journal Labs, 2024)
This study aims to obtain empirical evidence about the effect of profitability and capital structure moderated by free cash flow on firm value. The research object is a company included in the classification of the raw material industry sector which is listed on the Indonesia Stock Exchange. The variables used as proxies for profitability return on assets (ROA) and return on equity (ROE); the capital structure variable is proxied by the debt to assets ratio (DAR) and the debt to equity ratio (DER), and the firm value is proxied by the price to book value (PBV). While the moderating variable uses free cash flow (FCF). Data analysis used multiple regression with the least squares method, and the sample selection method used purposive sampling. Based on the best model produced in this study, it is proven that free cash flow can significantly strengthen the effect of company profitability proxied by return on assets ROA and return on equity (ROE); the effect of capital structure proxied by DAR on firm value, but not as good as the direct effect of the moderated variables. The study reveals that profitability and capital structure significantly impact firm value, with free cash flow moderated by ROA. However, the model does not outperform direct effects, suggesting improved ROE, DAR management, and effective free cash flow management.